Motivations and segmentation of instagram users as a social network site: Their sociodemographic profiles, satisfaction and loyalty - Mauricio Carvache-Franco; Ana Beatriz Hernández-Lara; Orly Carvache-Franco; Wilmer Carvache-Franco (PLoS ONE, 2026)
Millions of Internet users interact daily with social network sites (SNS), and these figures are still expected to grow. This study aimed to identify the motivations and typology of different types of Instagram users, specifically pursuing these objectives: (1) to identify the motivations that lead individuals to use Instagram as a SNS; (2) to establish user segments based on these motivations; (3) to determine how these segments relate to user satisfaction and loyalty; and (4) to explore the relationship between the identified segments and key socio‑economic and demographic variables. The study was carried out through an online survey composed of 369 participants. For data analysis, factorial analysis, the K-means segmentation method, and the Chi-square test were used. Four motivational dimensions in the use of Instagram were identified, related to “Curiosity, Creativity, and Documentation,” “Self-expression,” “Socialization,” and “Recreation.” In addition, three distinct segments of Instagram users were identified based on their underlying motivations: “Enthusiasts”, “Spectators”, and “Passive Users”. Among them, the Enthusiasts emerged as the group displaying the highest levels of satisfaction and loyalty within the platform. The study further assessed the socio-economic and demographic profiles of each segment. This study offers original value by categorizing users based on their motivations, examining how these motivations relate to satisfaction and loyalty, and identifying the socio-economic and demographic profiles of the different user segments. The findings contribute to strategic frameworks for digital marketing and audience segmentation, providing organizations and businesses, particularly those that use Instagram as a communication, sales, or business channel, with actionable insights. Overall, this research establishes a solid foundation for future studies and practical applications in social media strategy, consumer behavior, and digital marketing.